Rancang Bangun Alat Pendeteksi Formalin dan Boraks pada Daging Bakso Berbasis Mikrokontroler - Dwy Sandy; Wendhi Yuniarto; Rusman Rusman (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
This study aims to design and implement a microcontroller-based instrument for detecting formaldehyde and borax in meatballs using an Arduino Uno. The instrument employs an HCHO gas sensor to detect formaldehyde and a TCS34725 color sensor to identify borax through changes in RGB values. The detection results are processed by the microcontroller and displayed through a 16×2 LCD, LED indicators, and a buzzer. Experimental tests were performed using five formalintreated samples and five borax test samples. The HCHO sensor produced average readings of 1.36, 9.86, 18.71, 23.61, and 48.09 ppm for 1–5 ml formalin, respectively. The TCS34725 also showed distinguishable RGB patterns on direct meatball samples and test papers. The developed instrument can function as an initial screening tool for food safety testing.